2020
DOI: 10.1136/flgastro-2019-101321
|View full text |Cite
|
Sign up to set email alerts
|

Patient experience of gastrointestinal endoscopy: informing the development of the Newcastle ENDOPREM™

Abstract: BackgroundMeasuring patient experience is important for evaluating the quality of patient care, identifying aspects requiring improvement and optimising patient outcomes. Patient Reported Experience Measures (PREMs) should, ideally, be patient derived, however no such PREMs for gastrointestinal (GI) endoscopy exist. This study explored the experiences of patients undergoing GI endoscopy and CT colonography (CTC) in order to: identify aspects of care important to them; determine whether the same themes are rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(76 citation statements)
references
References 38 publications
2
74
0
Order By: Relevance
“…In this study, a pathway variation was apparent, with some patients gaining direct access to testing, whilst others were surprised by initial specialist appointments before being sent for tests. This has also been identified in an endoscopy patient experience study 58 and highlights a potential area for improvement, as previous literature has identified that a straight‐to‐test protocol results in a reduction in times to cancer diagnosis and cancer treatment 59,60 . In addition, GP direct access testing performed as well as, and on some measures better than, consultant‐triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction 61 …”
Section: Discussionmentioning
confidence: 60%
“…In this study, a pathway variation was apparent, with some patients gaining direct access to testing, whilst others were surprised by initial specialist appointments before being sent for tests. This has also been identified in an endoscopy patient experience study 58 and highlights a potential area for improvement, as previous literature has identified that a straight‐to‐test protocol results in a reduction in times to cancer diagnosis and cancer treatment 59,60 . In addition, GP direct access testing performed as well as, and on some measures better than, consultant‐triaged testing on measures of disease detection, appropriateness of referrals, interval from referral to testing, and patient and GP satisfaction 61 …”
Section: Discussionmentioning
confidence: 60%
“…The identification of those at highest risk of colorectal neoplasia can translate into earlier diagnosis of advanced colorectal neoplasia, thereby improving patient outcomes based on the well-established association between earlier stage of CRC at diagnosis and better long-term outcomes, in addition to the importance of identifying and removing precancerous lesions 24 . Avoidance of colonoscopy in those at low risk of colorectal neoplasia will reduce exposure to an unpleasant procedure, which can be associated with substantial anxiety, pain or discomfort as well as carrying a risk (albeit small) of haemorrhage, perforation, other adverse events and even death 25 27 . With the advent of COVID-19, endoscopy avoidance also reduces infection risk in patients, many of whom are in high-risk groups for serious COVID-19 outcomes 28 , 29 .…”
Section: Benefits Of Risk Stratificationmentioning
confidence: 99%
“…The explanatory value of the ten regression analyses is relatively low, although the regression analysis for 'worry before the examination' (Q4), 'discomfort during colonoscopy' (Q5), 'pain during colonoscopy' (Q6) and 'worry about the result' (Q7) may explain some of the variance of outcome variable better than the other regression analyses. This means that additional factors not captured in our questionnaire may be important for the colonoscopy experience, for example, the bowel preparation [13,31], patients' expectations, the ability to choose appointment and/or examination methods, embarrassment [15,31], environmental factors at the endoscopy unit as well as factors related to the endoscopist [13] and endoscopy assistant [19]. The generalizability to other age groups may not be relevant since all participants were 60 years, although the age range is not that wide in CRC screening.…”
Section: Limitationsmentioning
confidence: 99%
“…Other factors for the colonoscopy experience are related to the endoscopist, such as the technical skills, manner, and gender, and the nursing staff, such as the explanation of the procedure and the post-procedure discussion [14]. The role of the endoscopy assistant has also been indicated to have an impact on the endoscopy experience in terms of information and communication [15], pain and conscious sedation during the colonoscopy [16], Women, individuals with lower education, and those with intensity of religious practice have a greater wish for an endoscopist with the same gender [17,18]. However, choosing gender of the endoscopist was not considered important in a qualitative study by Nielsen et al [15], but still, individuals, especially men reported that they felt more embarrassed when the endoscopist was of the opposite gender.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation